PID Control for a Two-Axis Orientable Solar Panel System - Roldán Mckinley, Javier; Fernández Pizarro, Andrés; Beltrán González, Jaison (Scientia et Technica, 2019)
The control of a two degree-of-freedom Orientable Solar Panel System-OSPS was simulated for a control scheme that combines Proportional, Integral and Derivative actions with a computed torque control inner loop. The latter controller calculates the torques at the joints. Two plants of the dynamic model of the OSPS were evaluated: analytical and Simmechanics. Three case motions were simulated: random, to a sef position, and end-of-the-day cycle. Controller gains were set by using the sustained oscillation Nichols-Ziegler second syntonization method. It was found that in order to save energy along the motion the non-underdamped behavior is required. This is attained by setting the integral component gain to zero. Very small maximum theoretical position errors of the azimuth and elevation position angles suggest that the combination PD-CTC scheme is satisfactory for controlling the OSPS motion along day